Injectable hydrogel regulates immune infiltration through physical and chemical synergy in the treatment of steroid-induced osteonecrosis of the femoral head - Zherui Fu; Yiwen Xu; Fangqi Xu; Haoyu Zhou; Na Lin; Ning Zhang; Feng Lin (Materials Today Bio)
The incidence of steroid-induced osteonecrosis of the femoral head (SONFH) is increasing annually; however, the underlying pathological mechanism remains unclear, which is an obstacle to its effective treatment. The negative effect of immune infiltration on the physiological activity of focal stem cells is one potential mechanism that has attracted attention. It is difficult to simulate the complex regulation of the interaction system between immune cells and stem cells using a single regulation method. In this study, we demonstrated that the immune infiltration of T helper 17 (Th17) cells plays an important role in the progression of SONFH. Based on this finding, we developed an injectable hydrogel system with both physical and chemical synergistic regulatory properties to enhance the activity of stem cells using electrical stimulation. This treatment was designed to prevent the infiltration of Th17 cells by regulating the physiological function of stem cells and blocking the negative effect of Th17 cells on stem cells pharmacologically. Thus, the dual synergistic regulation of immune infiltration at the lesion site of SONFH enhanced the physiological activity and function of the stem cells, thereby improving the therapeutic effect of SONFH. This hydrogel system provides insight for the future development of multifactorial regulatory systems and provides a strategy for the treatment of SONFH.